Potentials Of Financial Distress Before And During Covid-19 Pandemic In Food And Beverage Companies Listed On The Indonesia Stock Exchange - Nurfauziah; Nadiya Nafisamuna (Publisher Cv. Inara, 2022)
The study aims to determine the level of financial distress in food and beverage companies listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 pandemic. The model used is the Zmijewski and Springate models. The research used is comparative quantitative research. The samples taken are all food and beverage companies in Indonesia listed on the Indonesia Stock Exchange (IDX) for the 2019 and 2020 period, which are 32 companies. The Bank's financial report data is taken through the IDX's official website, namely https://www.idx.co.id. The expected results in this study are more food and beverage companies experiencing financial distress during the Covid-19 pandemic than before the Covid-19 pandemic and there are potential differences in financial distress before and during covid-19 in food and beverage companies.